What Type of Incision for Anterior Cervical Spine Surgery Involving Long Segments Can Bring Better Cosmetic and Functional Outcomes? - Lee, Hyung Rae; Lee, Dong-Ho; Seok, Sang Yun; Park, Sehan; Cho, Jae Hwan; Hwang, Chang Ju; Lee, Choon Sung (Neurospine, 2022)
Objective: To determine whether double transverse incisions could provide superior cosmetic and functional outcomes, including rates of dysphagia and dysphonia, compared with longitudinal incisions in patients undergoing anterior cervical spine surgery (ACSS) involving ≥ 3 levels.Methods: A total of 62 consecutive patients who underwent ACSS involving ≥ 3 levels were included in this study. They consist of 33 with longitudinal incisions (L group) and 29 with double transverse incisions (DT group). We recorded functional outcome measures including the Bazaz score for postoperative dysphagia and the Voice Handicap Index-10 (VHI-10) for postoperative dysphonia. The Vancouver Scar Scale (VSS) and the patient and observer scar assessment scale (POSAS) were used to evaluate postoperative skin scarring.Results: Cosmetic results, as assessed using the VSS and POSAS, were significantly better in the DT than in the L group at most follow-up time points (p < 0.01 each). Dysphagia rates were significantly lower in the DT group than in the L group during the late postoperative period from 6 months until final 2 years of follow-up (p < 0.01 each). There were no significant different results between the 2 groups in terms of dysphonia.Conclusion: A double transverse incision can be a feasible option when performing ACSS involving ≥ 3 levels, providing better cosmesis and lower rates of persistent dysphagia than with a longitudinal incision.